Perancangan Freshwater Aquarium Park Di Indragiri Hulu Dengan Pendekatan Arsitektur Hemat Energi - Ardy Fhadly; Wahyu Hidayat; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Freshwater Aquarium Park in Indragiri Hulu accommodate different types of aquatic fauna and ecosystem (natural) that provides an overview of the life of freshwater without having to dive can be used as a means of recreation, education and conservation. Indragiri Hulu as a region with a thousand rivers, has the potential of fish and aquatic plants, which is not yet fully developed and there are no facilities to accommodate its Indragiri aquatic ecosystems. This design apply the principle of energy-efficient architecture with the concept of multi expression unity of design. The application of this concept in the design of Freshwater Aquarium Park that analogy as root produce different shapes on each side of the building, penzoningan which facilitate inter-space function that applies the principles of energy saving by optimizing the air, light, and water. The integration between the air system of artificial and natural, system of artificial and natural light and the synergy between passive and active methods. This building with filtration maximize water conservation and ecosystem modeling.Keywords: Energy Saving, Multi Expression, Freshwater Aquarium Park, Indragiri Hulu